Analisis Penerimaan Aplikasi Transportasi Online di Kepulauan Riau Menggunakan Metode Technology Acceptance Model - Mangapul Siahaan; Kelvin Kurniawan (Politeknik Negeri Batam, 2022)
Traffic density in the Riau Islands area is increasing day by day. Population density that has exceeded this threshold causes congestion on the road which causes losses to people who are carrying out activities. As e-commerce grows rapidly, it becomes a push for e-commerce applications that develop in line with the community's need for online application-based services that operate on smartphones. The application of online application-based transportation services that are growing rapidly. One of the factors of this online application-based transportation service innovation is the growing number of internet services offered by internet service providers and more and more internet users, so that the internet becomes a necessity and lifestyle for the community. This research is a development of previous research in examining the factors that influence public acceptance of online transportation applications using the UTAUT2 research model; the current study uses the Technology Acceptance Model research model. This questionnaire was distributed to 400 respondents to the residents of the Riau Islands using Amos and SPSS. The results of the analysis of transportation application online acceptance in Riau Kepulauan using Technology Acceptance Model were seen from the construct of behavioral intention use to attitude toward using is 100%, actual system use to behavioral intention to use is 94.7%, perceived usefulness to perceived ease of use is 80.3%, attitude toward using to perceived usefulness is 47.6% whereas behavioral intention use to perceived usefulness is not effected as positive.